Effects of Enzyme Loading and Immobilization Conditions on the Catalytic Features of Lipase From Pseudomonas fluorescens Immobilized on Octyl-Agarose Beads - Arana-Peña, Sara; Rios, Nathalia S.; Carballares, Diego; Mendez-Sanchez, Carmen; Lokha, Yuliya; Gonçalves, Luciana R. B.; Fernandez-Lafuente, Roberto (Frontiers in Bioengineering and Biotechnology, 2020)
Abstract The lipase from Pseudomonas fluorescens (PFL) has been immobilized on octyl-agarose beads under 16 different conditions (varying pH, ionic strength, buffer, adding some additives) at two different loadings, 1 and 60 mg of enzyme/g of support with the objective of check if this can alter the biocatalyst features. The activity of the biocatalysts versus p-nitrophenyl butyrate and triacetin and their thermal stability were studied. The different immobilization conditions produced biocatalysts with very different features. Considering the extreme cases, using 1 mg/g preparations, PFL stability changed more than 4 folds, while their activities versus pNPB or triacetin varied a 50-60%. Curiously, PFL specific activity versus triacetin was higher using highly enzyme loaded biocatalysts than using lowly loaded biocatalysts (even by a 2 fold factor). Moreover, stability of the highly loaded preparations was higher than that of the lowly loaded preparations, in many instances even when using 5ºC higher temperatures (e,g., immobilized in the presence of calcium, the highly loaded biocatalysts maintained after 24 h at 75ºc a 85% of the initial activity, while the lowly loaded preparation maintained only 27% at 70ºC). Using the highly loaded preparations, activity of the different biocatalysts versus pNPB varied almost 1.7 folds and versus triacetin 1.9 folds. In this instance, the changes in stability caused by the immobilization conditions were much more significant, some preparations were almost fully inactivated under conditions where the most stable one maintained more than 80% of the initial activity. Results suggested that immobilization conditions greatly affected the properties of the immobilized PFL, partially by individual molecule different conformation (observed using lowly loaded preparations) but much more relevantly using highly loaded preparations, very likely by altering some enzyme-enzyme intermolecular interactions. There is not an optimal biocatalyst considering all parameters. That way, preparation of biocatalysts using this support may be a powerful tool to tune enzyme features, if carefully controlled.